Analysis of The Influence of Price, Quality of Service, Facilities and Location on Customer Satisfaction at Cafe Dapur Kampung, Marbau District - Apriyani Syahfitri; Zulkarnaen Nasution; Fauziah Hanum (PT Mattawang Mediatama Solution, 2023)
This study aims to determine the Effect Analysis of Price, Service Quality, Facilities, and Location on Consumer satisfaction at the café Dapur Kampung, Marbau district. Based on the results of the research conducted, there is a significant effect simultaneously between the independent variables (Price, Service Quality, Facilities, and Location) affecting the dependent variabel (customer satisfaction). This is evidenced by the obtained F count value of 25.199 which is greater than the F table value of 2.47. in adition, it is partially known that price (X1) has a positive and significant effect on consumer satisfaction (Y). this is evidenced by obtaining a t count value value that is greater than t table (2.693 > 1.983) and a coeffecient value of 0.284 and a positive sign. Service quality (X2) has a positive and significant effect on customer satisfaction (Y). this is evidenced by obtaining a t count value that is greater than t table (2.530 > 1.983) and a coefficient value of 0.132 and a positive sign. Facilities (X3) have a positive and significant effect on customer satisfaction (Y). this is evidenced by the obtained t count value which is greater than t table (2.153 > 1.983) and a coefficient value of 0.212 and a positive sign and location (X4) has a positive and significant effect on consumer satisfaction (Y). this is evidenced by obtaining a t count value that is greater than t table (3.530 > 1.983) and a coefficient value of 0.327 and a positive sign